Aktualisasi Keterampilan Berbicara Melalui Metode Tebak Kata dalam Pembelajaran Bahasa Indonesia pada Siswa Kelas II di SDI Sabilil Huda - Mega Dwi Susanti; Linda Lailatul Rohmah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The purpose of this research is to improve the breeding ability of grade II students of SDI Sabilil Huda Bukaan. This type of research is class action research (PTK) conducted in two cycles. Each cycle consists of stages of planning, action, observation, and reflection. The subjects in this study were grade II students of SDI Sabilil Huda as many as 23 children. data collection methods conducted by researchers are observations, tests, interviews, and documentation. The result of the study is that the Actualization of Guess the Word Method has increased. The conclusion in this study is that it has improved this can be seen from the students' learning outcomes at pre-cycle 70.91, in the cycle, I experienced an average increase of 78.52, in cycle II experienced an average increase of 86.13. Pre-cycle completion, cycle I, cycle II increased in a row from 26.07% increased to 69.91% increased again to 100%. As well as the observations of teachers and students have been carried out well.